Übungsbuch : Allgemeine und Anorganische Chemie. - Riedel, Erwin (De Gruyter Studium., 2015)
Hundreds of challenging and varied exercises and solutions in organic chemistry provide undergraduate chemistry students and students with chemistry as a minor field with comprehensive exam preparation. The third, fully revised edition includes detailed explanations of solutions methods and numerous illustrations.